PEGARUH METODE DAN LAMA FERMENTASI TERHADAP MUTU MOL (MIKROORGANISME LOKAL) - Juanda Juanda; Irfan Irfan; Nurdiana Nurdiana (Jurnal Floratek, 2011)
MOL (Local Microorganism) is one of the key factors to determine the success in manufacturing of organic fertilizer. MOL can fully substitute EM4 (Effective Microorganism) widely being sold in market, as starter to accelerate composting process. The MOL in the experiment was produced from agricultural waste likes in consumable fruits. The experiment was aimed to investigate a better fermentation method in the production of MOL. A Split Plot Design with fermentation methods (with and without applying of air channel) as main plot and length of fermentation (0, 1, 2, 3, 4 and 5 weeks) as sub-plot were applied to produce MOL, with 2 replications. With air channel, the gas produced from the fermentation process could be channeled out of the fermentation container. Analysis of MOL quality included total microorganisms (TCC), temperature, pH, and color. In general, result showed that the MOLs produced from fermentations without air channel were better than the ones produced from with air channel. The highest amount of TCC in MOL was produced from 3 weeks fermentation without air channel.